2013
DOI: 10.1007/s00253-013-5411-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel GAPDH-derived antimicrobial peptides secreted by Saccharomyces cerevisiae and involved in wine microbial interactions

Abstract: Saccharomyces cerevisiae plays a primordial role in alcoholic fermentation and has a vast worldwide application in the production of fuel-ethanol, food and beverages. The dominance of S. cerevisiae over other microbial species during alcoholic fermentations has been traditionally ascribed to its higher ethanol tolerance. However, recent studies suggested that other phenomena, such as microbial interactions mediated by killer-like toxins, might play an important role. Here we show that S. cerevisiae secretes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 24 publications
4
127
1
Order By: Relevance
“…The killer toxin did not seem to be produced. Toxic peptides that had been described in wineries [10,11] could be present. Our results, without completely discarding other possibilities, point to the great importance of oxygen for the performance and even viability of K. lactis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The killer toxin did not seem to be produced. Toxic peptides that had been described in wineries [10,11] could be present. Our results, without completely discarding other possibilities, point to the great importance of oxygen for the performance and even viability of K. lactis.…”
Section: Discussionmentioning
confidence: 96%
“…Several factors have been referred to justify this early death of the non-Saccharomyces species (NS) in wineries, such as the high levels of ethanol and organic acids, low pH values, depletion of certain nutrients, as well as other yeast-yeast interactions (e.g. killer toxins) [10,11]. The limited oxygen availability is another factor mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Albergaria et al (2010) showed that S. cerevisiae CCMI 885 started to secrete three antifungal peptides of about 6, 4.5 and 4 kDa at the end of the AF exponential growth phase (day 2) with a gradual increase of their concentration during the stationary growth phase (days 4 and 7). Later on, Branco et al (2014) who used the same yeast strain demonstrated that these peptides were also active against the growth of O. oeni and corresponded to GAPDH-derived peptides of 1.6 kDa. They suggested that the peptides were released by apoptotic yeast cells during the stationary phase.…”
Section: 2mentioning
confidence: 96%
“…forming membrane pores and facilitating the entry of SO 2 inside the cells thus leading to the bacterial death and arrest of MLF. The mechanism of action of the GAPDH-derived peptides identified by Branco et al (2014) and that inhibited the growth of O. oeni was not elucidated. In addition no data concerning the malate consumption was shown.…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation